ANALISIS DISKRIMINAN DALAM MEMPREDIKSI KINERJA PERBANKAN DI INDONESIA - Sumarlin Sumarlin; Annisa Juniarta Musda; Alim Syariati (Master of Management, Mataram University, 2019)
This study aims to determine the contribution of financial ratios into the classification of banks’ performance into good, fairly good and less good by using discriminant analysis. This research is quantitative with data amounted from 34 banks. The results of five banking financial ratios that can distinguish the status of the banking performance level is CAR, ROA, ROA and NPL. Four variables have a significant influence in differentiating the well-performing banks, the fairly good and less good. First equation to predict differences in banking groups is Non-Performing Loan. Second discriminant equation shows that the ratio predicting the most dominant group differences is ROA.